2018
DOI: 10.3389/fmicb.2018.00456
|View full text |Cite
|
Sign up to set email alerts
|

Research on Volatile Organic Compounds From Bacillus subtilis CF-3: Biocontrol Effects on Fruit Fungal Pathogens and Dynamic Changes During Fermentation

Abstract: The dynamic changes of the levels of volatile organic compounds (VOCs) produced by Bacillus subtilis CF-3 and their biocontrol effects on common fungal pathogens were researched in this study. The results showed that the VOCs in 24-h fermentation liquid (24hFL) of B. subtilis CF-3 inhibited mycelial growth of Botrytis cinerea, Colletotrichum gloeosporioides, Penicillium expansum, Monilinia fructicola, and Alternaria alternata, with a mean inhibition rate of 59.97%. The inhibitory effect on M. fructicola and C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 36 publications
2
63
0
Order By: Relevance
“…There are differences in sensitivity to these compounds among fungal species 50,51 . Thus, optimal treatments for different fungal pathogens will be different.…”
Section: Discussionmentioning
confidence: 99%
“…There are differences in sensitivity to these compounds among fungal species 50,51 . Thus, optimal treatments for different fungal pathogens will be different.…”
Section: Discussionmentioning
confidence: 99%
“…The two plates were superimposed with Parafilm around the edges to prevent the leakage of air and incubated at 25°C. The mycelial diameter was measured after 5 days, and the rate of inhibition of radial mycelial growth was calculated using the equation published by Gao et al (2018). Three replicates were used for each treatment, and the experiment was repeated thrice.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial volatiles are typically small low‐molecular weight (0·1–0·5 kDa) compounds having up to 20 carbon atoms with a lipophilic moiety, high vapour pressure and low boiling point. Using headspace solid‐phase microextraction combined with gas chromatography‐mass spectrometry (HS‐SPME‐GC‐MS), Gao et al () identified 74 different volatile organic compounds (VOC) from B. subtilis CF‐3 of which ketone, acids, ethers and phenols were predominant. Among these VOC, 2,4‐di‐tert‐butylthiophenol and benzothiazole had strong inhibitory effect against Monilinia fructicola and C. gloeosporioides (Gao et al ).…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…Using headspace solid‐phase microextraction combined with gas chromatography‐mass spectrometry (HS‐SPME‐GC‐MS), Gao et al () identified 74 different volatile organic compounds (VOC) from B. subtilis CF‐3 of which ketone, acids, ethers and phenols were predominant. Among these VOC, 2,4‐di‐tert‐butylthiophenol and benzothiazole had strong inhibitory effect against Monilinia fructicola and C. gloeosporioides (Gao et al ). Massawe et al () reported 16 different types of VOC from three different species of Bacillus and eight of these VOC could inhibit the growth of S. sclerotiorum .…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%